Physical characterization and analysis of tissue inflammatory response of the combination of hydroxyapatite gypsum puger and tapioca starch as a scaffold material - Amiyatun Naini; Dessy Rachmawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Cases of bone damage in the oral cavity are high, up to 70% of which consist of cases of fracture, tooth extraction, tumor, and mandibular resection. The high number of cases of bone damage will cause the need for bone graft material to increase. The bone graft material that we have developed is a combination of hydroxyapatite gypsum puger (HAGP) and tapioca starch (TS) scaffold. Purpose: This study analyzes the physical characterization and tissue inflammatory response of the combination of HAGP+TS as a scaffold for bone graft material. Methods: Eighteen Wistar rats were used. HAGP+TS were installed into the molar 1 socket for 7 and 14 days. First, HAGP was evaluated using XRF and SEM before setting up the in vivo experiment. A blood sample was drawn and then tested for TNF-α levels using ELISA. Results: The XRF revealed that the main constituents of hydroxyapatite were Ca and P. Next, SEM characterization on the HAGP+TS showed an average pore size of 112.42 µm2, which is beneficial for cell activity to grow as new bone tissue. In addition, TNF-α on days 7 and 14 on the HAGP+TS scaffold did not elicit an inflammatory response. Conclusion: The combination of HAGP+TS contains a high amount of Ca and also has excellent interconnectivity between pores. It also does not trigger an inflammatory response in the tissue; therefore, it is a good candidate as an alternative bone graft material.